Limites e possibilidades do letramento escolar: um estudo etnográfico das práticas de leitura e das capacidades de linguagem nas disciplinas curriculares - Suzana dos Santos Gomes (2010)
This doctoral dissertation presents the results of the analysis of reading practices of teachers of Portuguese, English, Arts, Geography, History, Science and Mathematics at two local public secondary schools. 1 examined the extent to which discursive practices adopted by teachers influenced the development of reading skills in temis of understanding, assessment, and replication of the text. The primary guidelines for this research were Bakhtin's theories of enunciation and speech genres (1929, 1952-1953/1979), the theoretical framework of Vygotsky (1930,1934,1935) on human development, learning and mediation; and the postulates of Heath (1982,1983), Street (1984, 1993, 1995) and Barton & Hamilton (1998. 2000) on literacy. The research was developed on the basis of interactional ethnography and considered the contributions of Castanheira, Crawford, Dixon & Green (2001). In theanalysis, I observed the types of discourse used in the classroom, the ways of reading and the mediating role of the teacher in the discursive practices among students in order to identify evidence of the reading skills taught / learned in the classroom. The results showed the limitsand possibilities of school literacy, reaffimied the urgency of teacher education in the field of literacy and discourse genre in order to create both a school reading project undertaken by all areas of knowledge and the demand for greater investment in public policies to encouragereading in the school context and out of school.